Case Report: Rapid and progressive left ventricular endocardial calcification in an infant with Williams syndrome - Zhou, Jie; Liu, Dan; Chen, Jiao (Frontiers in Pediatrics, 2024)
Williams syndrome (WS) is characterized by a range of clinical features, including cardiovascular disease, distinctive facial traits, neurobehavioral disorders, and a condition known as transient infantile hypercalcemia. Among these, endocardial calcification represents a non-specific response to severe, etiologically diverse myocardial injuries. In this report, we document a unique case involving an infant with WS who exhibited rapidly progressive arterial stenosis and left ventricular endocardial calcification, associated with a novel heterozygous deletion. While arterial stenosis is the most frequently observed cardiovascular issue in WS, instances of endocardial calcification during infancy are exceedingly rare and have not previously been reported in the context of WS 1